Perspectives Of Brain Research (Educational Neuroscience) on the Design and Implementation of Teaching Strategies in Educational Technology - Alkhassawneh, Sani; Al Sharif, Houria (Journal of neuroeducation, 2025)
The amalgamation of educational neuroscience and educational technology generates novel prospects for improving the understanding and efficacy of pedagogical approaches. By analyzing the brain's engagement with many educational technologies, educators can develop more effective instructional strategies customized to students' requirements. This approach can yield substantial enhancements in academic performance and offer varied and thorough learning experiences. This research investigates the influence of findings from educational neuroscience on the development and implementation of instructional strategies within educational technology. Analyze the amalgamation of educational technology with concepts from educational neuroscience and contrast conventional learning theories with those grounded on neuroscience. Present the empirical evidence supporting the improvement of learning outcomes through neuroscience-informed pedagogical approaches, as well as the challenges and constraints related to the application of educational neuroscience in educational technology.